Novel genetic tools for Clostridia and a synthetic biology approach to control spore formation in process organisms - Cañadas Blasco, Ines Cristina (2019)
Through the application of engineering principles, synthetic biology provides the means to harness the power of living things for the good of humankind. Central to this discipline is the ability to create systems through the assembly of standardised biological parts that may be incorporated into living cells. As a consequence, such synthetic chassis are endowed with biological properties of limitless, beneficial potential in applications as divergent as medicine, energy, food production and the environment.